2022
DOI: 10.1021/acs.analchem.2c03367
|View full text |Cite
|
Sign up to set email alerts
|

Single Nanoparticle Counting-Based Liquid Biopsy for Cancer Diagnosis

Abstract: Liquid biopsy has become a sought-after technique for disease diagnosis because it provides real-time, dynamic, and comprehensive information that can alleviate the dilemmas faced by tissue biopsy. Multiplexed microRNAs (miRNAs) have been demonstrated to be promising biomarkers in liquid biopsy but fall short in providing simple and sensitive analytical methods. In this work, we established a novel nanoparticle counting strategy to accomplish simultaneous analysis of three breast cancer-associated miRNAs for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Similar results were obtained from the two methods; that is, miR-10b concentrations were not significantly different among the three tumors, whereas the expression of miR-155 was significantly higher in liver cancer than in the other cancer types (Figure G and H). This reveals that our method has comparable detection capability with that of RT-PCR and also shows the limitations of using a single miRNA to diagnose and differentially diagnose tumors . We also validated the versatility of our strategy for longer target detection, such as the conserved 60 nt sequence of DENV-2.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Similar results were obtained from the two methods; that is, miR-10b concentrations were not significantly different among the three tumors, whereas the expression of miR-155 was significantly higher in liver cancer than in the other cancer types (Figure G and H). This reveals that our method has comparable detection capability with that of RT-PCR and also shows the limitations of using a single miRNA to diagnose and differentially diagnose tumors . We also validated the versatility of our strategy for longer target detection, such as the conserved 60 nt sequence of DENV-2.…”
Section: Resultsmentioning
confidence: 55%
“…This reveals that our method has comparable detection capability with that of RT-PCR and also shows the limitations of using a single miRNA to diagnose and differentially diagnose tumors. 34 We also validated the versatility of our strategy for longer target detection, such as the conserved 60 nt sequence of DENV-2. The length of the Bstem was optimized (Figure S20), and a comparison of the specificity and sensitivity between different padlock structures indicated that the DSLP also exhibited superior capability (Figure 5I).…”
Section: Resultsmentioning
confidence: 61%
“…Besides, the expression levels of one or more circulating miRNAs are commonly used as important diagnostic and prognostic indicators for diseases in noninvasive detection. Currently, many techniques have been applied for miRNA detection such as real-time quantitative polymerase chain reaction, northern blotting, nanopore, inductively coupled plasma mass spectrometry, and microarray-based techniques . Despite high sensitivity, these approaches are hampered by expensive equipment, elaborate sample processing, and professional skills .…”
Section: Introductionmentioning
confidence: 99%
“…Liquid biopsies are a less wounded approach to monitor trace amounts of cancer biomolecules with lower expense, which just use serums and are patient-amiable, presenting great potential for high-efficiency diacrisis and prognosis of tumors . MicroRNA (miRNA) is the nonprotein-encoded ultrasmall molecular weight RNA nucleotide, which exists in the peripheric serum or plasma and expresses strong correlation with cancers. , Hence, it becomes a prevalent biomarker for liquid biopsies, but improvement is needed to detect exceedingly trace amounts of miRNAs and to avoid misdiagnosis . Currently, technologies exist to detect miRNAs including the microarray, bead-supported assay, and quantitative PCR .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Hence, it becomes a prevalent biomarker for liquid biopsies, but improvement is needed to detect exceedingly trace amounts of miRNAs and to avoid misdiagnosis. 13 Currently, technologies exist to detect miRNAs including the microarray, 14 bead-supported assay, 15 and quantitative PCR. 16 Nevertheless, these methods are largely in the inchoate development phases, and there are substantial aspects for further exploratory optimization.…”
Section: ■ Introductionmentioning
confidence: 99%